Lessons for students in architecture. - Hertzberger, Herman, 1932- (Rotterdam : 010, 2005)
The work of Herman Hertzberger is the subject of wide international esteem. 1991 first saw publication of Hertzberger's Lessons for Students in Architecture, an elaborated version of lectures he had given since 1973 at Delft University of Technology. In it, the background to his work and the ideas underlying it are put into words by the architect himself. It presents a broad spectrum of subjects and designs, with practical experience and evaluation of the use of these buildings serving as a leitmotif. This immensely successful book has gone through many reprints and has also been published in Japanese, German, Italian, Portuguese, Taiwanese, Dutch, Greek and Chinese. More than 750 illustrations give a broad insight into Hertzberger's 'library' and a stimulating impression of the influences and sources of inspiration of one of the Netherlands' major postwar architects. Geïllustreerd met 763 (!) interessante afbeeldingen, geeft de tekst een duidelijk inzicht in de multiculturele voorbeelden en invloeden die de context vormen voor het werk van Hertzberger. Geschikt voor studenten architectuur, maar zeker ook voor de geïnteresseerde. Biblion, April 11th 2002
Keywords: Architectuur